2009
DOI: 10.1111/j.1365-2923.2009.03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the multiple mini-interview: a qualitative analysis

Abstract: We gained a deeper understanding of participants' experiences of a high-stakes, decision-making process for selection into a graduate-entry medical school. We discuss our findings in the light of the existing literature and make recommendations to address the issue of differing participant expectations and understandings of the MMI, and to improve the credibility and acceptability of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 16 publications
7
66
0
Order By: Relevance
“…For admission to the School of Pharmacy at the University of Toronto, 47% of applicants felt six-minute stations were 'just right' and 50% 'a bit short', for the eight-minute stations 50% indicate they were 'just right' and 43% 'a bit long' (Cameron & MacKeigan 2012). Kumar et al (2009) report that applicants to the School of Medicine, Sydney University, commented that stations were not long enough which resulted in a pressure to speak more quickly. Twenty-three percent of applicants to the School of Medicine, University of California, Los Angeles (UCLA), were of the opinion that the eight-minute per station MMI was well timed, with 47% indicating they were too short and 30% indicating they were too long.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…For admission to the School of Pharmacy at the University of Toronto, 47% of applicants felt six-minute stations were 'just right' and 50% 'a bit short', for the eight-minute stations 50% indicate they were 'just right' and 43% 'a bit long' (Cameron & MacKeigan 2012). Kumar et al (2009) report that applicants to the School of Medicine, Sydney University, commented that stations were not long enough which resulted in a pressure to speak more quickly. Twenty-three percent of applicants to the School of Medicine, University of California, Los Angeles (UCLA), were of the opinion that the eight-minute per station MMI was well timed, with 47% indicating they were too short and 30% indicating they were too long.…”
Section: Timingmentioning
confidence: 99%
“…Interviewers indicated that they perceive the MMI to be a fair selection tool Kumar et al 2009;Razack et al 2009;Dowell et al 2012) but some have concerns regarding how stressful it may be for applicants (Kumar et al 2009;Dowell et al 2012).…”
Section: Timingmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Across these settings, the MMI seems to be a useful admissions tool for measuring professional attributes. In a systematic review of studies exploring MMI use for student selection in health professions training, Pau et al concluded that candidates and interviewers found the process acceptable and fair.…”
Section: Introductionmentioning
confidence: 99%
“…Candidates remain at each station for a few minutes, and assessors rate them using a structured rubric. 4,5 Although the MMI is valuable, it requires considerable personnel resources, and the regimented interaction between interviewers and candidates poses its own limitations. 5 BEI has increased in popularity as a tool to better understand residency applicants' personal and workrelated experiences.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Although the MMI is valuable, it requires considerable personnel resources, and the regimented interaction between interviewers and candidates poses its own limitations. 5 BEI has increased in popularity as a tool to better understand residency applicants' personal and workrelated experiences. 6 Because of its success rate in predicting future on-the-job behavior compared to traditional interviewing, 7 BEI has been endorsed by residency program directors.…”
Section: Introductionmentioning
confidence: 99%